2012
DOI: 10.1029/2011je003913
|View full text |Cite
|
Sign up to set email alerts
|

Far‐ultraviolet reflectance properties of the Moon's permanently shadowed regions

Abstract: 1] Although of great interest for science and resource utilization, the Moon's permanently shadowed regions (PSRs) near each pole present difficult targets for remote sensing. The Lyman Alpha Mapping Project (LAMP) instrument on the Lunar Reconnaissance Orbiter (LRO) mission is able to map PSRs at far-ultraviolet (FUV) wavelengths using two faint sources of illumination from the night sky: the all-sky Ly a glow produced as interplanetary medium (IPM) H atoms scatter the Sun's Ly a emissions, and the much faint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
143
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(162 citation statements)
references
References 39 publications
(59 reference statements)
18
143
1
Order By: Relevance
“…LEND found that the epithermal neutron flux was significantly suppressed in some polar regions outside PSR's, inferring the presence of hydrogen-bearing materials in regions that regularly experience some level of solar irradiation (Mitrofanov et al, 2012). Beginning in the mid-latitudes, results from NIR spectroscopy, far ultra-violet (FUV) and epithermal neutron observations indicate trends that are consistent with the interpretation poleward increases in hydrogen concentration (Feldman et al, 1998;McCord et al, 2011;Gladstone et al, 2012;Litvak et al, 2012;Hendrix et al, 2012;Li et al, 2012). From LEND results, Mitrofanov et al (2012) postulated a correlation between the poleward decrease in the epithermal neutron flux and solar irradiation.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…LEND found that the epithermal neutron flux was significantly suppressed in some polar regions outside PSR's, inferring the presence of hydrogen-bearing materials in regions that regularly experience some level of solar irradiation (Mitrofanov et al, 2012). Beginning in the mid-latitudes, results from NIR spectroscopy, far ultra-violet (FUV) and epithermal neutron observations indicate trends that are consistent with the interpretation poleward increases in hydrogen concentration (Feldman et al, 1998;McCord et al, 2011;Gladstone et al, 2012;Litvak et al, 2012;Hendrix et al, 2012;Li et al, 2012). From LEND results, Mitrofanov et al (2012) postulated a correlation between the poleward decrease in the epithermal neutron flux and solar irradiation.…”
Section: Introductionsupporting
confidence: 65%
“…(b) The determination of a nearly-symmetric latitude dependent contrast in epithermal neutron count rates on equator and pole-facing slopes suggests that pole-facing slope hydration is occurring over most of the Moon's upper latitudes and provides partial support for upper-latitude hydration findings described by Sunshine et al (2009), McCord et al (2011 and Li and Milliken (2013). (c) Although these analyses were limited to the south and only considered latitudes 45-90°S, the results showed that the highest contrast (EFS-PFS) in hydrogen concentrations was near the poles, similar to NIR, UV and neutron results (Feldman et al, 1998;Mitrofanov et al, 2012;McCord et al, 2011;Gladstone et al, 2012). Though not evaluated here, the polar results may, at least partly, be driven by the slopes of polar PSR's.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, some multibounce craters in polar areas, which might contain ice deposits as well as rough surface terrain, do have interiors in permanent darkness and are extremely cold, according to Diviner thermal maps [Paige et al, 2010b]. Examples of this latter category include Shackleton [see also the results of Thomson et al, 2012b;Gladstone et al, 2012;Zuber et al, 2012] and a fresh crater on the floor of Rozhdestvensky (Figure 3; Table 3). It is possible for a fresh crater at the poles to contain ice if the timescales of ice accumulation (probably on the order of 10 5 -10 7 years) exceed the likely timescales of geological erosion of its surface ejecta deposits (~10 8 -10 9 years).…”
Section: Modeling the Radar Backscatter Of Rough And Icy Cratersmentioning
confidence: 99%
“…In contrast, the spatial distribution and depth dependence of lunar polar hydrogen concentrations are not well correlated with locations of volatile thermal stability. For example, while surface frost has been observed in most lunar PSRs [13], bulk hydrogen concentrations do not appear to be uniformly enhanced within PSRs [14,15], and are not well correlated with locations of volatile stability expected by surface and subsurface temperatures in polar regions [16]. This qualitative difference between the lunar and mercurian PSRs, despite their similar environmental conditions (e.g., temperature, temporal stability), is not understood.…”
Section: Introductionmentioning
confidence: 94%